Current practices and goals for mean arterial pressure and spinal cord perfusion pressure in acute traumatic spinal cord injury: Defining the gaps in knowledge - Menacho, Sarah T. (J Spinal Cord Med, 2019)
Context: The mainstay of treatment for acute traumatic spinal cord injury (SCI) is to artificially elevate the patient’s mean arterial pressure (MAP) to >85 mmHg to increase blood flow to the injured spinal cord for 7 days. However, the literature supporting these recommendations are only Class III evidence. In fact, the critical time window in which to elevate MAP after SCI and the optimal vasopressor to use are largely unknown, as is whether cerebrospinal fluid diversion has a role, and this leads to variability among practitioners. Also undefined is whether manipulating these parameters improves neurological outcome. Objective: Our goal is to better delineate current clinical practice and identify gaps in knowledge surrounding the care of patients with traumatic SCI. Methods: We undertook a systematic review of the current literature identified from PubMed on MAP elevation and spinal cord parenchymal pressure in acute SCI. Results: The 8 articles (6 human; 2 porcine) that met our inclusion criteria were all published within the last 6 years. Four were prospective, 1 was retrospective, and 3 were review articles. Only one study was randomized. All of these studies involved small sample sizes and varying lengths of MAP elevation. Choice of vasopressor was variable as well. Conclusions: From our literature review, we posit that norepinephrine may be the vasopressor of choice, that spinal parenchymal pressure monitors can be safely placed at the injury site, and that the combination of MAP elevation and cerebrospinal fluid drainage may improve neurologic outcome more than either intervention alone.